Vestibular Morphological Alterations in Adolescent Idiopathic Scoliosis: A Systematic Review of Observational Studies - Irene Cortés-Pérez; Lourdes Salamanca-Montilla; Francisca Gámiz-Bermúdez; Esteban Obrero-Gaitán; Alfonso Javier Ibáñez-Vera; Rafael Lomas-Vega (MDPI AG, 2022)
Adolescent idiopathic scoliosis (AIS) is the most frequent pediatric spinal deformity. Its treatment still shows limited results due to the existent lack of knowledge regarding etiopathogenesis. Thus, the purpose of the study is to check the existence of vestibular morphological alterations among idiopathic scoliosis patients. To meet the objective, we performed this systematic review searching studies in PubMed Medline, SCOPUS, Web of Science, CINAHL Complete and SciELO until 15 September 2022. Articles that analyzed the morphology of the vestibular apparatus were selected, comparing subjects with AIS versus healthy subjects. Variables were selected that measured the orientation of the channels as well as the general conformation of the vestibular apparatus. One hundred and eighty-five records were retrieved in the preliminary searches, of which five studies were finally included, providing data from 154 participants (83 cases and 71 healthy controls) with a mean age 16.07 ± 2.48 years old. Two studies conclude that the superior and lateral semicircular canals are longer and thinner in patients with AIS. One study concluded that the measure between centers of superior and lateral canals and the angle whose vertex is placed the center of posterior canal were significantly shorter in subjects with AIS than in healthy controls in the left-side of vestibular apparatus. Two studies found an asymmetry in the verticality of the lateral canals on both sides in subjects with AIS, although it is not clear whether the left canal is in a more horizontal or vertical position. Patients with AIS seem to present morphological asymmetries of the vestibular apparatus, fundamentally on the left side. These anomalies seem to correlate with the location of the curve but not with its laterality or severity.